Influence of habitat heterogeneity on the assemblages and shell use of hermit crabs (Anomura: Diogenidae) - Teoh, Hong Wooi; Muhammad Ali Syed Hussein; Chong, Ving Ching (Academic Sinica, 2014)
Background